A comparative assessment of nutritional and health status between tribal and nontribal under five children of Mysore, India - Sarjapura V Divakar (Muller Journal of Medical Sciences and Research, 2013)
Context and Aim: The tribal populations are recognized as socially and economically vulnerable; thereby patterns and trends in tribal areas are required to monitor local epidemics and to assess the effectiveness of public health programs in prevention and control of diseases. This prompted us to assess the health status and morbidity pattern among the tribal and non-tribal population of Mysore. Settings and Design: A cross sectional study was carried in the forest areas of Mysore in the 33 tribal hamlets present. Materials and Methods:Among 33 tribal hamlets, a random selection of 18 hamlets was performed by lottery method. A pre-tested structured interview was used for data collection through house to house visits by individual and family scheduling. Data were statistically analyzed using measures of central tendency, standard normal test (Z), and Chi-square test (χ2 ). P-value of <0.05 was considered statistically significant. All the tests were performed using Smith′s Statistical Software version 2.80. Results: The study revealed more of tribal (45.03%) children compared to non-tribal (22.47%) were suffering from protein energy malnutrition with P < 0.001 and 7.35% of tribal children were severely malnourished. Among tribal under five children, morbidity pattern observed was more with skin infections (31.33%), followed by (21.20%) dental caries; (19.20%) intestinal infections; (21.85%) while in non-tribal counterparts, skin infections were (12.98%), (7.78%) dental caries; (17.98%) intestinal infections; (25.84%) respiratory infections; and (20.22%) vitamin deficiencies. Conclusion: Tribals have low socio-economic status, poor nutritional status, increased prevalence of morbid conditions compared to non-tribal population. Further detailed research surveys among tribal population would be invaluable.